2022
DOI: 10.1016/j.xphs.2021.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biological Evaluation of Curdlan-Poly(Lactic-Co-Glycolic Acid) Nanoparticles as a Host-Directed Therapy Against Mycobacterium Tuberculosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…The study also revealed that curdlan has a high affinity for Dectin-1 receptors ( D'Souza et al, 2022 ), giving an advantage in delivering anti-TB therapeutics and AICs directly to macrophages, enhancing drug payload on targeted cells while decreasing immunotoxicity. Furthermore, the study demonstrated that the produced nanosystem was non-toxic, necessitating future research as a host-directed treatment therapy for Mtb intracellular elimination ( D'Souza et al, 2022 ).
Fig.
…”
Section: Nanoparticle-based Approaches For Hdt-tbmentioning
confidence: 99%
See 3 more Smart Citations
“…The study also revealed that curdlan has a high affinity for Dectin-1 receptors ( D'Souza et al, 2022 ), giving an advantage in delivering anti-TB therapeutics and AICs directly to macrophages, enhancing drug payload on targeted cells while decreasing immunotoxicity. Furthermore, the study demonstrated that the produced nanosystem was non-toxic, necessitating future research as a host-directed treatment therapy for Mtb intracellular elimination ( D'Souza et al, 2022 ).
Fig.
…”
Section: Nanoparticle-based Approaches For Hdt-tbmentioning
confidence: 99%
“…6 ) , compared to controls; compared to the RIF solution, Glu-CS-PLGA NPs delivered 4-fold more RIF into ALM ( Dube et al, 2014 ). Recent similar work by D’Souza et al found that curdlan functionalized PLGA NPs intended for host-directed therapy increased and accelerated the release of pro-inflammatory cytokine TNF-α in macrophages, resulting in lower intracellular Mtb levels within the macrophages ( D'Souza et al, 2022 ). The study also revealed that curdlan has a high affinity for Dectin-1 receptors ( D'Souza et al, 2022 ), giving an advantage in delivering anti-TB therapeutics and AICs directly to macrophages, enhancing drug payload on targeted cells while decreasing immunotoxicity.…”
Section: Nanoparticle-based Approaches For Hdt-tbmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the polysaccharide glucan stimulates macrophages to produce pro-inflammatory signals (ROS and reactive nitrogen species), including IL-12 and TNFα, which are known to be crucial in the control of Mtb [ 154 , 155 ]. More recently, it was shown that curdlan-loaded PLGA NPs with sizes between 330 nm and 453 nm significantly upregulated the pro-inflammatory cytokine TNF-α [ 156 ]. As a consequence, the NPs reduced the intracellular Mtb burden over 72 h in infected RAW264.7 macrophages.…”
Section: The Potential Of Nanoparticles Regarding the Treatment Of Tu...mentioning
confidence: 99%